Seed rain and seed limitation in a planted gallery forest in Brazil - Barbosa, Karina C.; Pizo, Marco A. (Blackwell Publishing, 2006)
With seeds collected monthly during one year from 53 1-m(2) seed traps, we investigated the seed rain and seed limitation in a gallery forest planted in 1994 in SE Brazil. Contrasting animal- (zoochorous) and wind-dispersed (anemochorous) plants we investigated (1) which aspects of the composition and structure of the vegetation influence the abundance and species richness of the seed rain; (2) if such influences differ between zoochorous and anemochorous seeds; (3) if the abundance and richness of the seed rain sampled under zoochorous and nonzoochorous plant species differ; and (4) if seed limitation (given by the proportion of sites to which seeds were not dispersed) differs between zoochorous and anemochorous plant species, and also between species that have been planted and those that further colonized the area (colonists). Seed rain was intense and dominated by anemochorous species. The overall seed rain was not influenced by the vegetation parameters we analyzed (canopy height and cover, plant size, abundance, and richness) or by the plant species above the seed trap. The abundance and richness of zoochorous seeds in a given spot was influenced by the abundance and richness of zoochorous plants in its immediate vicinity. Seed limitation was higher for anemochorous than zoochorous species and higher for planted than for colonist species. We concluded with recommendations for the initial establishment of a planted forest, including the homogeneous distribution of zoochorous plants to permit a spatially homogeneous zoochorous seedfall, which will likely enhance the chances of survival and successful establishment of seeds.
Keywords: anemochory; restored forest; seed dispersal; seed limitation; zoochory